WOMEN'S SELF-HELP GROUPS - ROLE IN POVERTY NEXUS AND EMPOWERMENT - Irshad Ahmad Reshi (CV. Radja Publika, 2023)
Self help groups have been working for the empowerment of women since its inception. In its system for destitution lightening and women empowerment, the government of India has given significant space to women's self help groups What are the Characteristics of the women based gathering models of neediness easing and women empowerment that are being actualized in the nation? How are the poor women composed into groups? How do the group work? Also, what has been the commitment of these models to destitution lightening and women empowerment? Secondary data are used for addressing these issues .SHGs help in poverty alleviation and SHGs contribute in fighting covid 19aswell. This paper highlights the role of SHGs in Women Empowerment.